2014
DOI: 10.3390/f5030425
|View full text |Cite
|
Sign up to set email alerts
|

Soil Carbon Dynamics in Residential Lawns Converted from Appalachian Mixed Oak Stands

Abstract: Abstract:The conversion of unmanaged forest land to homesites dominated by managed turfgrass lawns continues to increase and has large potential impacts on biogeochemical cycling. The conversion process from forest into mowed turfgrass involves a major disturbance to soil properties and shift in ecological conditions, which could affect soil physical, chemical and biological properties, including carbon sequestration. We conducted a study on 64 residential properties, ranging from 5 to 52 years since developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 44 publications
3
18
1
Order By: Relevance
“…The higher BD under row crop systems than unmanaged systems (Table 1) is expected and is likely associated with 20 to 25 yr of conventional tillage (Arshad et al, 1999; Jabro et al, 2009). Research on forestland conversions to lawns agrees with our finding that the turfgrass sites had greater BD than the unmanaged areas (Campbell et al, 2014).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The higher BD under row crop systems than unmanaged systems (Table 1) is expected and is likely associated with 20 to 25 yr of conventional tillage (Arshad et al, 1999; Jabro et al, 2009). Research on forestland conversions to lawns agrees with our finding that the turfgrass sites had greater BD than the unmanaged areas (Campbell et al, 2014).…”
Section: Resultssupporting
confidence: 88%
“…Our finding of a higher SOC concentration in turfgrass systems compared with row crop systems (Table 1) could be due to the C input to soils as grass clippings (Qian et al, 2003, 2010). The SOC buildup in turfgrass system could also be due to the high amounts of dense fibrous grass root systems, which have regular turnover and greater lignin and hemicellulose contents than leaves (Campbell et al, 2014). Therefore, the roots decompose at a slower rate than leaves and help in SOC buildup.…”
Section: Resultsmentioning
confidence: 99%
“…Golubiewski (2006) studied soil C change in urban green space along a decadal chronosequence after urbanization and found that soil C density recovered and surpassed that of the surrounding native grasslands in the second decade after establishment. For lawns established on previously forested soils in Virginia, USA, there was a positive relationship between the time since development and surface (0–0.1 m) soil C concentration but a negative relationship at 0.2 to 0.3 m ( p = 0.03), perhaps as soil C in the previous ecosystem was mineralized (Campbell et al, 2014). Bae and Ryu (2015) observed a large 2.5‐fold increase in soil C over 10 yr in a new and intensively managed urban park in Seoul.…”
Section: Discussionmentioning
confidence: 99%
“…Soil BD was sampled from 0-15 and 15-30 cm depths using a soil-cutting ring of 5.3 cm in diameter and then was determined as the moisture-corrected (oven-dried at 105 • C) mass of each sample divided by the measured volume of the excavated soil core (Campbell et al, 2014). Prior to soil property and nutrient analyses, roots and litter were removed from the soil samples by hand and then air-dried, crushed, and passed through a 2 mm mesh sieve.…”
Section: Soil Samples Analysismentioning
confidence: 99%